Diagnoza nieprzystosowania społecznego nieletnich w Anglii i Walii - Muskała, Maciej (My University, 2014)
Diagnosis of being an integral part of the rehabilitation process is the preliminary stage. Adequately to well-defined needs, possibilities and conditions of the juvenile can be appropriately adjusted the measures of influence. In Anglo-Saxon literature, the effects of disorders of the socialization process, the degree of anti-social behavior described by risk levels. The problem is meet at the Polish ground with growing interest as theorists and practitioners. This article presents tools for the diagnosis of the degree of anti-social behavior juveniles.
The diagnosis of juvenile anti-social behavior in England and Wa les
Keywords: diagnoza; nieletni; szacowanie ryzyka